Correlation of Serum Cu and Zn with Some Cytokines in Major Depressive Disorder - Hussein Kadhem Al-Hakeim (Journal of Global Pharma Technology, 2020)
There is an association of major depressive disorder with different changes in the immune functioning which associate with activation of inflammatory processes. Trace elements such as copper (Cu) and zinc (Zn) have many physiological functions. In the present study, serum levels of Cu, Zn, inflammatory (IL-6), and anti-inflammatory (IL-10) cytokines have been measured in MDD patients and compared with the apparently healthy group. The correlation between the measured trace elements and IL-6 and IL-10 is another purpose of the study to find out the trace elements effect on the secretion of the interleukins in MDD patients. The study involved 60 pretreatment males with MDD and 30 apparently healthy as controls (age matched). The results indicated that there was significantly increase (p